2010
DOI: 10.1007/s11745-010-3386-3
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Plasma, Erythrocytes and Adipose: Their Correlations and Effects of Age and Sex

Abstract: The composition of fatty acids in abdominal subcutaneous adipose tissue and the correlation of fatty acid values of plasma and erythrocytes had not been reported in Japan. The aim of the present study was to investigate the fatty acid composition and correlation of plasma and erythrocyte phospholipids (PL) and adipose triacylglycerols (TG) in 75 adult patients admitted for non-malignant diseases. We also examined the relationship of n-3 and n-6 polyunsaturated fatty acid (PUFA) with patients' characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
3
28
0
2
Order By: Relevance
“…That age and sex showed a significant impact on PUFA levels will be important to assess further. The positive correlations found between each of the three PUFAs and age are consistent with the findings of previous reports [13,14]. The association between PUFAs and PTSD should now be explored in a well-designed observational study; if the observed association is judged to be causal, intervention trials will then be needed to elucidate causality.…”
Section: Tablesupporting
confidence: 87%
“…That age and sex showed a significant impact on PUFA levels will be important to assess further. The positive correlations found between each of the three PUFAs and age are consistent with the findings of previous reports [13,14]. The association between PUFAs and PTSD should now be explored in a well-designed observational study; if the observed association is judged to be causal, intervention trials will then be needed to elucidate causality.…”
Section: Tablesupporting
confidence: 87%
“…This finding has been noted in some previous studies 8,10,13,14,32 but not in others. 9,12 Some researchers consider that this reflects higher consumption of seafood by women than by men; however, this was not the case in the present study.…”
Section: Discussionsupporting
confidence: 50%
“…It is also unclear whether 8.3 is a critical inflection point or not. However, 8.3 is a possible value for elderly Japanese people at least 24 . Further large-scale studies are required to determine whether there is a suitable range of serum ARA levels for P300 components because there was the limitation that the number of participants in this study was small.…”
Section: Discussionmentioning
confidence: 99%